The role of segmental mass and moment of inertia in dynamic-contact task construction. - Brown, N. A.; Jensen, J. L. (Journal of Motor Behavior, 2006)
The authors examined whether differences between children and adults in the application of muscle forces during a dynamic-contact task (cycling) can be attributed to children's relatively lower segmental mass and moment of inertia. They examined pedal-force construction as adults and younger and older children (n = 7 in each group), with and without mass added to their limbs, pedaled an appropriately scaled bicycle ergometer. When mass was added to their limbs, children adjusted muscular forces on the pedal in a way that began to approach the pattern demonstrated by adults. Because age, neuromotor maturation, and motor experience were held constant, it seems plausible that by 6 to 8 years of age, and perhaps younger, physical size and growth limit children's production of adult-like muscle forces on the pedal.